2018
DOI: 10.1021/acs.jafc.8b02559
|View full text |Cite
|
Sign up to set email alerts
|

Pinostrobin Inhibits Proprotein Convertase Subtilisin/Kexin-type 9 (PCSK9) Gene Expression through the Modulation of FoxO3a Protein in HepG2 Cells

Abstract: Pinostrobin, a flavonoid phytochemical found in variety of plants, has been demonstrated to possess numerous bioactivities such as antioxidant, anti-inflammatory, anticancer, and neuroprotective properties. The aim of this study was to investigate the hypocholesterolemic effect of pinostrobin on the regulation of the gene expression of PCSK9 and its underlying mechanisms in hepatic cells. We found that pinostrobin (20 and 40 μM) significantly inhibited the PCSK9 promoter activity from 1.00 ± 0.16 (fold) to 0.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Our conclusion is supported by the following lines of evidence: (1) Among 59 tumor TMA samples, the high EGFR staining group is largely associated with the low staining group of LXR-α, and vice versa; (2) Among prostate cell lines tested, there is a general tendency of inversed protein levels between EGFR and FOXO3A. FOXO3A could induce cholesterol regulation and lipid management (52), and be regulated by EGFR (44)(45)(46); (3) EGFR inhibitor Afatinib inhibited p-AKT and increased FOXO3A and LXR-α, as did AKT inhibitor LY294002; (4) The levels of endogenously expressed LXR-α were increased upon FOXO3A transfection, while they were reduced by FOXO3A knockdown; and (5) Overexpression of FOXO3A elevated the level of LXR-α mRNA, and vice versa.…”
Section: Discussionsupporting
confidence: 71%
“…Our conclusion is supported by the following lines of evidence: (1) Among 59 tumor TMA samples, the high EGFR staining group is largely associated with the low staining group of LXR-α, and vice versa; (2) Among prostate cell lines tested, there is a general tendency of inversed protein levels between EGFR and FOXO3A. FOXO3A could induce cholesterol regulation and lipid management (52), and be regulated by EGFR (44)(45)(46); (3) EGFR inhibitor Afatinib inhibited p-AKT and increased FOXO3A and LXR-α, as did AKT inhibitor LY294002; (4) The levels of endogenously expressed LXR-α were increased upon FOXO3A transfection, while they were reduced by FOXO3A knockdown; and (5) Overexpression of FOXO3A elevated the level of LXR-α mRNA, and vice versa.…”
Section: Discussionsupporting
confidence: 71%
“…Among these FoxO proteins, FoxO3a is a predominant player in the regulation of cholesterol homeostasis in hepatic cells. It has been reported that the loss of FoxO3a leads to increased lipid synthesis in the liver [25,50]. In hepatic FoxO3-deficient mice, both the hepatic and plasma cholesterol levels were increased.…”
Section: Discussionmentioning
confidence: 94%
“…Tai et al [37] reported that curcumin reduced PCSK9 via down regulating HNF1α. FoxO TFs have been reported to play an important role in several essential cellular functions including cell proliferation, apoptosis, lipid metabolism and liver function [25,48,49]. Among these FoxO proteins, FoxO3a is a predominant player in the regulation of cholesterol homeostasis in hepatic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schltr., Zingiberaceae], was studied with respect of its potential influence on PCSK9. The treatment of HepG2 with 20 and 40 µM of pinostrobin led to a dose-dependent reduction of mRNA and protein expression of PCSK9, and a reduction of its catalytic activity, resulting in increased LDLR expression and LDL uptake by the cells [113]. Stereospecific differences in the pharmacokinetic profile of pinostrobin have been observed in rats after iv and oral administrations (Figure 1 and Table 1) [114].…”
Section: Other Polyphenolsmentioning
confidence: 97%